KAJIAN HUKUM TERHADAP KEDUDUKAN BANK SELAKU PEMEGANG HAK TANGGUNGAN ATAS BERAKHIRNYA SERTIPIKAT HAK GUNA BANGUNAN DIATAS HAK PENGELOLAAN (HPL) YANG MENJADI OBJEK JAMINAN (STUDI : PT BANK INTERNASIONAL INDONESIA, TBK CABANG MEDAN DIPONEGORO) - MELKI SUHERY SIMAMORA (PREMISE LAW JURNAL, 2014)
ABSTRACT Bank as one of the financing institutions, which help streamline of debtors’ business through lending an amount of money in the form of credit, has the main function in the economic growth. The theory used in the research Legal Certainty (Rechtssicherheit) theory. The bank as the holder of Hypothecation, when the period of the validity of the Building Rights certificate ends, which is located on the Management Rights, which is still a collateral, initially has the position as preferential creditor and the holder of hypothecation because the Deed for the Giving of Hypothecation (APHT) as the collateral has absolute, droit de suite, droit de preference, specialty, and publicity principles. There are some obstacles related to the annulment of the Building Rights Certificate as the collateral for a certain debt which occurs to the Bank as the holder of hypothecation in which the annulment of the Building Rights Certificate on the Management Rights becomes the Bank’s collateral. Keywords: Hypothecation, Building Rights, Management Rights.